Water ways - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Environmental Flows for River Systems conference, to be held in Cape Town, South Africa, from 3 to 8 March 2002, will focus on the sustainable use of all parts of river systems as well as subsistence use of their resources.Southern Waters...